Implementation Of Food Diversification And Security Program Through Local Food Festivals (B2sa) By Food Crops And Horticulture Departement, East Kalimantan Province - Amelia, Eka Ratna; Istamala, Nadia; Oktavia, Ellisa Wulan; Paselle, Enos (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2024)
Food security is where food is sustainably available, accessible, safe to consume, and affordable. In 2023, the province will hold the B2SA Local Food Festival, which the government and community hope will create a healthy generation. This research has two objectives: a). to describe and analyze the implementation of the Program for Increasing Diversification and Food Security Towards Diverse, Nutritious, Balanced and Safe Food (B2SA) through the 2023 East Kalimantan Local Food Festival. b). To describe and analyze the inhibiting and supporting factors for implementing the Program for Increasing Diversification and Food Security Towards Diverse, Nutritious, Balanced, and Safe Food (B2SA) through the 2023 East Kalimantan Local Food Festival. This research uses descriptive qualitative methods. The research location was the Food Crops and Horticulture Service of East Kalimantan Province. This research shows that the Local Food Festival (B2SA) in East Kalimantan Province is a good step in overcoming dependence on rice and wheat. The importance of consuming diverse foods can be increased through education and promotion of B2SA, including using the East Kalimantan Local Food Festival (B2SA). 2023 as a platform to disseminate relevant information. The implementation of the 2023 Provincial B2SA Local Food Festival by the East Kalimantan Province Food, Food Security and Horticulture Service has paid attention to dependent variables, which include essential stages in the policy implementation process to improve the nutritional quality and food security of the community as a whole, and in changing patterns. Food consumption has become more diverse, nutritious, balanced, and safe (B2SA).